2016
DOI: 10.1039/c5cc06934c
|View full text |Cite
|
Sign up to set email alerts
|

The increased CO2 adsorption performance of chitosan-derived activated carbons with nitrogen-doping

Abstract: Highly porous nitrogen-doped activated carbons (NACs) were prepared by the chemical activation of chitosan using alkali carbonates. The NACs exhibited extremely high CO2 capacities of 1.6 mmol g(-1) (15 kPa) and 4.9 mmol g(-1) (100 kPa) at 25 °C. Nitrogen atoms doped into carbon frameworks clearly enhanced CO2 adsorption at low partial pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 36 publications
3
58
0
Order By: Relevance
“…The presence of nitrogen enhances the interactions between activated porous biocarbon and CO 2 resulting in higher isoelectric heats of adsorption. 18,52,53 It is proposed that a higher content of nitrogen tends to shi the process of CO 2 adsorption from just van der Waal's interactions to somewhat stronger physical forces such as pole-pole interactions 54 and hydrogen bonding. 55 Aer the CO 2 adsorption, the spent activated porous biocarbon materials were easily regenerated by heating under vacuum up to a temperature of 250 C and then retested for CO 2 uptake.…”
Section: Co 2 Adsorption Analysismentioning
confidence: 99%
“…The presence of nitrogen enhances the interactions between activated porous biocarbon and CO 2 resulting in higher isoelectric heats of adsorption. 18,52,53 It is proposed that a higher content of nitrogen tends to shi the process of CO 2 adsorption from just van der Waal's interactions to somewhat stronger physical forces such as pole-pole interactions 54 and hydrogen bonding. 55 Aer the CO 2 adsorption, the spent activated porous biocarbon materials were easily regenerated by heating under vacuum up to a temperature of 250 C and then retested for CO 2 uptake.…”
Section: Co 2 Adsorption Analysismentioning
confidence: 99%
“…[8][9][10] A number of different porous materials such as mesoporous silica MCM-41, SBA-15, porous carbons, zeolites and metal organic frameworks (MOFs) and their amine functionalized versions have been investigated as solid adsorbents. [3][4][5][6][7][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]28 Sayari and co-workers have extensively studied the adsorption of CO 2 over pure mesoporous silica with an ordered porous structure at different temperatures and pressures. They realised that the surface functional groups on the mesoporous materials are the key to enhance the adsorption of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In the other approach, porous carbons are treated with suitable amines. 18 A further activation procedure for N doped carbons is oen attempted to increase the surface area using different acids such as H 3 PO 4 , HNO 3 or alkalis such as KOH. 19 It has been found that the incorporation of N atom in the carbon matrix results in a signicant improvement in the adsorption of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A suitable CO 2 adsorbent should have a high specific surface area, a high porosity with proper pore sizes, a favorable surface chemistry, and a high chemical/ mechanical stability. Many CO 2 adsorbents based on different materials, such as zeolites (Banerjee et al 2009;Cavenati et al 2004;Kongnoo et al 2017;Ojuva et al 2013), silica gels (Arellano et al 2016), activated carbon (Fujiki and Yogo 2016;Roberts et al 2017;Singh et al 2017), and metal-organic frameworks (An and Rosi 2010;Millward and Yaghi 2005;Salehi and Anbia 2017), have been investigated in recent decades. However, adsorbents based on these materials have some drawbacks, such as their high cost, complex preparation methods, toxicities, and the use of corrosive materials during their preparation.…”
Section: Introductionmentioning
confidence: 99%